2016
DOI: 10.1103/physrevb.93.155164
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects on magnetic ground states in cobalt-doped multiferroicMn1xCoxWO4

Abstract: Using ambient pressure x-ray and high pressure neutron diffraction, we studied the pressure effect on structural and magnetic properties of multiferroic Mn1−xCoxWO4 single crystals (x = 0, 0.05, 0.135 and 0.17), and compared it with the effects of doping. Both Co doping and pressure stretch the Mn-Mn chain along the c direction. At high doping level (x = 0.135 and 0.17), pressure and Co doping drive the system in a similar way and induce a spin-flop transition for the x = 0.135 compound. In contrast, magnetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Those works have found that pressure is able to disrupt the fine equilibrium of the frustrated antiferromagnetic phase of MnWO 4 (AF1) but enhance the Néel temperature of the AF3 and AF4 magnetic phases of pure or lowly Co-doped MnWO 4 and highly Co-doped MnWO 4 , respectively. Considering the direct effect that pressure has on the spin structure that is even able to cause a spin-flop transition for highly Co-doped MnWO 4 [59], one can expect a new and fascinating phase diagram in the HP phase of MnWO 4 , where distortions are expected to be higher due to the lowering of symmetry from space group P2/c to P1. So far, the only study done in this direction has been done with CuWO 4 ; according to calculations in that study, the structural phase transition from P2/c to P1 also involves an antiferromagnetic to ferromagnetic order [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those works have found that pressure is able to disrupt the fine equilibrium of the frustrated antiferromagnetic phase of MnWO 4 (AF1) but enhance the Néel temperature of the AF3 and AF4 magnetic phases of pure or lowly Co-doped MnWO 4 and highly Co-doped MnWO 4 , respectively. Considering the direct effect that pressure has on the spin structure that is even able to cause a spin-flop transition for highly Co-doped MnWO 4 [59], one can expect a new and fascinating phase diagram in the HP phase of MnWO 4 , where distortions are expected to be higher due to the lowering of symmetry from space group P2/c to P1. So far, the only study done in this direction has been done with CuWO 4 ; according to calculations in that study, the structural phase transition from P2/c to P1 also involves an antiferromagnetic to ferromagnetic order [60].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some works have appeared to deal with the pressure-temperature magnetic phase diagram of pure [9,58] or cobalt alloyed [59] MnWO 4 . Those works have found that pressure is able to disrupt the fine equilibrium of the frustrated antiferromagnetic phase of MnWO 4 (AF1) but enhance the Néel temperature of the AF3 and AF4 magnetic phases of pure or lowly Co-doped MnWO 4 and highly Co-doped MnWO 4 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The desired spin-orbitlattice coupling can be enhanced by introducing chemical pressures and magnetic anisotropy into the frus trated zigzag chains of the spin system in MnWO 4 . This can be further controlled by applying external electric and magn etic fields [6,34,35] or under pressure [36]. For instance, according to [37], in Mn 1−x Co x WO 4 the chiral spin order is preserved at domain boundaries between two chemical zones around x = 0.15 (helical AF5 and conical AF2/AF4 domains).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years some works have appeared dealing with the pressure-temperature magnetic phase diagram of pure [58] or cobalt alloyed [59] MnWO4. Those works have found that pressure is able to disrupt the fine equilibrium of the frustrated antiferromagnetic phase of MnWO4 (AF1) but enhance the Néel temperature of the AF3 and AF4 magnetic phases of pure or lowly Co-doped MnWO4 and highly Co-doped MnWO4, respectively.…”
Section: Discussionmentioning
confidence: 99%